A statistical study of pre‐summer hourly extreme rainfall over the Pearl River Delta metropolitan region during 2008–2017. (2nd January 2020) - Shou, Yi‐Xuan; Gao, Wenhua; Lu, Feng
Abstract: In this study, we explored the hourly extreme rainfall over the Pearl River Delta metropolitan region (PRDMR) by performing a statistical analysis on a 10‐year hourly precipitation dataset combined with the fifth generation of ECMWF atmospheric hourly reanalysis (ERA‐5) and half‐hourly FengYun‐2 geostationary satellite observations during the pre‐summer rainy season from 2008 to 2017. Results showed that hourly extreme rainfall events over the PRDMR increased at a significant pace during the most recent 10 years, which frequently occurred during the early morning (0400–0900 local standard time [LST; UTC + 8 hr]) and afternoon (1300–1800 LST) over the central urban district and 100‐km downstream area. Comparative analysis of the meteorological conditions between the two peak periods revealed that the hourly extreme rainfall events over the PRDMR during the pre‐summer rainy season were overall prefrontal rainstorms that occurred under the influence of dominant south‐westerlies and weak easterly backflows of warm‐moist air at lower atmospheres. The hot plumes rooted at the urban surface may be the key local environmental factors responsible for generating hourly heavy rainfall over the PRDMR. Given favourable large‐scale conditions, the interaction of urban heat island effects with sea breezes and mountain‐valley breezes can promote convection by altering the thermodynamic and dynamic structures around the PRDMR. By comparison, the hourly extreme rainfall events that occurred during morning periods over the PRDMR were more sensitive to moderate to strong wind shear at the lower planetary boundary layer, whereas those that occurred during afternoon periods were more likely to occur in the presence of an environment with high conditional instability. Abstract : In response to global warming, the frequency of extreme rainfall has experienced significant increases and is expected to continue increasing in the future. As the biggest and most populous metropolitan area in China, the Pearl River Delta Metropolitan Region (PRDMR) experienced a fast growth of the extreme rainfall frequency at a speed of two events every one rainy season during year 2008–2017. They prefer to occur during morning and afternoon over the central urban district and its 100‐km downstream.